Log Files as a Tool for Improving Internet Dictionaries - Bergenholtz, Henning; Johnsen, Mia (HERMES - Journal of Language and Communication in Business, 2005)
In their advertisements, dictionary publishers often praise their dictionaries for taking into account the exact needs of the users. Until the beginning of the 1980s, however, no theoretical contributions on dictionary use were available, neither in the form of purely theoretical considerations nor in the form of empirical research. Since then, the situation has changed completely. Such a large number of user surveys have been carried out that it is no longer possible to give a complete overview. Nevertheless, this has led to no signiﬁcant improvement of the situation as the majority of these surveys are not related to concrete examples of dictionary use. The surveys, which have always been concerned with printed dictionaries, have therefore not contributed to substantial improvements of dictionary conception. In the case of internet dictionaries, on the other hand, technical possibilities enable lexicographers to monitor user behaviour in a different and much more precise way. Analyses of log ﬁles reveal exactly which lemmas and which types of information have been requested, and, perhaps more signiﬁcantly, which lemmas and which types of information have been requested but were not found in the dictionary. Furthermore, log ﬁles allow lexicographers to see the types of information which have not, or not yet, been searched for. All in all, log ﬁles may thus be used as a tool for improving internet dictionaries – and perhaps also printed dictionaries – quite considerably.